y = (2x^2 - 10x - 6) / (2x^2 - x -3).

We need to find y-intercept of the curve y.

Then, we know that the y-intercept is the point where the curve meet the y-axis.

Then, the x-coordinates must be 0.

Then the point will be (0, y).

Let us substitute to find the values of y.

==> y= ( 2*0 - 10*0 - 6) / (2*0 - 0 - 3)

==> y= -6/ -3

==> y= 2

**Then the y-intercept is the point ( 0, 2)**

To find the y-intercept of a rational function we need to equate all the x in all the terms to 0 and see what the value of y is.

Here y = (2x^2 -10x -6 )/ (2x^2 - x - 3).

Substituting x with 0

=> y = (2*0^2 -10*0 -6 )/ (2*0^2 - 0 - 3)

=> y = ( 0 - 0 - 6) / (0 -0 -3)

=> y = -6/-3

=> y = 2

**Therefore the y intercept is at y = 2, x is equal to 0. So the point of the y-intercept is (0 , 2)**

To find the y intercept we put x= 0 in the given rational function,

(2x^2-10x-6)/(2x^20x-3).

=> y = (2*0^2-10*0-6)/((2*0^2-0-3)

=> y = -6/-3

=> y = 2.

Therefore the y intercept of the the rational function y = 2x2-10x-6/ (2x2-x-3) is y = 2.

Or the rational function y = 2x2-10x-6/ 2x2-x-3 intersects the y axis at (0 , 2).